Molecular investigation on infection by haemosporidians in three Western Palearctic species of swift (Apodidae) and their ectoparasitic louse flies - Luca Ilahiane; Roger Colominas-Ciurò; Pierre Bize; Giovanni Boano; Marco Cucco; Mauro Ferri; Giulia Masoero; Christoph M. Meier; Marco Pavia; Gloria Ramello; Gary Voelker; Irene Pellegrino (Parasitology Research, 2023)
Swifts (Apodidae) are an unusual group of birds that spend most of their lives in flight, landing only when breeding. Although this aerial lifestyle greatly reduces their likelihood of being bitten by vectors and infected by vector-born parasites, swifts can still be heavily infested during breeding by nest-based vectors such as louse flies (Hippoboscidae). Here, we investigated host, vector, and vector-borne parasite relationships in the three most widespread swift species in the Western Palearctic (WP): common swifts (Apus apus), pallid swifts (A. pallidus), and alpine swifts (Tachymarptis melba), their nest-based louse flies (Crataerina pallida and C. melbae) and avian haemosporidians (genera Haemoproteus, Plasmodium, and Leucocytozoon). Studies of haemosporidian infections in Apodidae remain limited, with clear evidence of infection found to date in just four Neotropical and one Australasian species. The possible role of louse flies in transmitting haemosporidian infections has never been tested in swifts. We assessed the occurrence of haemosporidian infection by PCR screenings of DNA from blood samples from 34 common swifts and 44 pallid swifts from Italy, and 45 alpine swifts from Switzerland. We also screened 20 ectoparasitic louse flies present on 20 birds and identified them by both morphological features and cytochrome oxidase subunit 1 (COI) barcodes. Our results provide no evidence of haemosporidian infection in the 123 swifts tested or in the two louse fly species we identified. Our findings are consistent with available knowledge showing no haemosporidian occurrence in WP swift species and that the most likely infection route for these highly aerial species (via louse fly ectoparasites during nesting) is unlikely.